Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Pegawai Dinas Perpustakaan Dan Kearsipan Provinsi DKI Jakarta - Nur Laila; Julinta Paulina; M. Asbullah (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
This study aims to determine the effect of work motivation and discipline partially and simultaneously on performance at the DKI Jakarta Provincial Library and Archives Service. The population used in this study were all employees of the DKI Jakarta Province Library and Archives Service, totaling 136 people. The data source used is primary data obtained through distributing questionnaires. While the data analysis techniques used are descriptive analysis, simple and multiple linear regression tests, correlation coefficient tests and Rsquare determination. Based on the results of the research test simultaneously the results of the analysis of variables (X1) Motivation, (X2) Work Discipline and (Y) Performance seen fcount of 29.877 with a ftable of 3.09 or 29.877 > 3.09 and the resulting significant value is 0.000 <0, 05. It is said that the variable Motivation, Work Discipline influences the performance of employees of the DKI Jakarta Provincial Library and Archives Service. The results of multiple regression analysis showed that the coefficient of determination at Adjusted Rsquare was 0.366 or 36.6%. This means that motivation and work discipline together have an effect of 36.6% on performance, 63.4% of changes that occur in employee performance can be explained by other variables outside this study.